2012
DOI: 10.3201/eid1810.111900
|View full text |Cite
|
Sign up to set email alerts
|

Scarlet Fever Epidemic, Hong Kong, 2011

Abstract: More than 900 cases of scarlet fever were recorded in Hong Kong during January–July, 2011. Six cases were complicated by toxic shock syndrome, of which 2 were fatal. Pulsed-field gel electrophoresis patterns suggested a multiclonal epidemic; emm12 was the predominant circulating type. We recommend genetic testing of and antimicrobial resistance monitoring for this reportable disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 5 publications
(5 reference statements)
4
41
0
Order By: Relevance
“…In the Far East, emm 1 and emm 4 isolates were the leading causes of scarlet fever in the late 1990s ( 6 ), although more recently, antimicrobial drug–resistant emm 12 S. pyogenes has dominated in this region ( 7 9 ). We found that the proportion of emm 12 isolates fell during the scarlet fever surge and found no antimicrobial drug resistance among emm 3 or emm 4 isolates associated with scarlet fever.…”
Section: Discussionmentioning
confidence: 99%
“…In the Far East, emm 1 and emm 4 isolates were the leading causes of scarlet fever in the late 1990s ( 6 ), although more recently, antimicrobial drug–resistant emm 12 S. pyogenes has dominated in this region ( 7 9 ). We found that the proportion of emm 12 isolates fell during the scarlet fever surge and found no antimicrobial drug resistance among emm 3 or emm 4 isolates associated with scarlet fever.…”
Section: Discussionmentioning
confidence: 99%
“…If both LM error and lag statistics reject the null hypothesis, the robust LM test can be applied. When both robust LM error and lag test statistics are highly significant, the analysis may select the model with the larger value of the statistics [52,53,54,55]. …”
Section: Methodsmentioning
confidence: 99%
“…It should be underlined that the choice of spatial lag or error models should not be based on statistical analysis, and it is actual previous theoretical knowledge [54,55]. If the omitted parameters are expected in a study due to unobservable spatially-correlated factors, then SEM models may be suitable.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment for 10 days with beta lactam antibiotic is enough even if the swollen tonsils and lymph nodes may take weeks to return to normal [14]. Scarlet fever attack in Hong Kong in 2011 was resistant to macrolides but still sensitive to beta lactams [15]. The most common associated complication of scarlet fever is Glomerulonephritis.…”
Section: Scarlet Fevermentioning
confidence: 99%